2006
DOI: 10.1176/ajp.2006.163.7.1187
|View full text |Cite
|
Sign up to set email alerts
|

Changing Profiles of Service Sectors Used for Mental Health Care in the United States

Abstract: How service sectors share responsibility for peoples' mental health care is changing, with more care falling to general medical providers rather than specialists. Efforts are required to ensure that people who would benefit have access to the necessary treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 262 publications
(162 citation statements)
references
References 43 publications
4
158
0
Order By: Relevance
“…Several studies have confirmed the prominent position of the medical specialty sector in providing services for mental disorders [41], even though the mental health specialty sector has been reported to be the major service sector for children and adolescents with mental disorders [13] and the most common subsequent service sector in adolescents entering the service system through the school mental health sector [18]. While mental health care in the medical specialty sector has improved over the past decade through a better understanding of mental disorders, the availability of practicable screening tools, provision of psychotherapy in these settings, and further development and promotion of psychotropic medications that are mostly prescribed by primary care physicians [24,42,43,44], most primary care pediatricians and child and adolescent psychiatrists believe that pediatricians should identify and refer, but not treat, their patients' mental health problems [45]. Indeed, the appropriateness of treatment of mental disorders in the medical specialty sector as compared to the mental specialty sector remains a matter of debate [46,47,48,49,50], which should be kept in mind when evaluating the referral patterns observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the prominent position of the medical specialty sector in providing services for mental disorders [41], even though the mental health specialty sector has been reported to be the major service sector for children and adolescents with mental disorders [13] and the most common subsequent service sector in adolescents entering the service system through the school mental health sector [18]. While mental health care in the medical specialty sector has improved over the past decade through a better understanding of mental disorders, the availability of practicable screening tools, provision of psychotherapy in these settings, and further development and promotion of psychotropic medications that are mostly prescribed by primary care physicians [24,42,43,44], most primary care pediatricians and child and adolescent psychiatrists believe that pediatricians should identify and refer, but not treat, their patients' mental health problems [45]. Indeed, the appropriateness of treatment of mental disorders in the medical specialty sector as compared to the mental specialty sector remains a matter of debate [46,47,48,49,50], which should be kept in mind when evaluating the referral patterns observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These questions asked them to describe key features of each topic discussed with the patient including (1) when the topic began and ended, (2) what the topic was about, and (3) how they felt on multiple affect dimensions. This response form was returned to the researcher for analysis.…”
Section: The Visit Reconstruction Methodsmentioning
confidence: 99%
“…access to and quality of mental healthcare exist, 13,14 and under-served communities with low provider availability may rely on alternative settings, such as faith-based 15,16 or substance abuse programs. 17,18 A recent Institute of Medicine report suggests that integrating heath and nonhealth services settings is essential to address chronic health needs.…”
Section: Main Measuresmentioning
confidence: 99%
“…8 Neighborhood poverty is predictive of depression onset, 9 and while prevalence of depressive disorders is similar for Latinos and African Americans relative to non-Hispanic whites, 10,11 African Americans may have greater severity when depressed. 12 Ethnic and socioeconomic disparities in access to and quality of mental healthcare exist, 13,14 and under-served communities with low provider availability may rely on alternative settings, such as faith-based 15,16 or substance abuse programs. 17,18 A recent Institute of Medicine report suggests that integrating heath and nonhealth services settings is essential to address chronic health needs.…”
mentioning
confidence: 99%